Manifestasi Adab di Ruang Siber: Redefinisi Literasi Digital melalui Kitab Adabul 'Alim Wal Muta'allim - Husnul Amin; Muhamad Alif Asshidiq (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Throughout time, understanding Digital Literacy has often been limited to technical skills: being able to operate a computer, knowing how to find information on Google, or simply understanding how to use applications. Digital literacy is not only about technological expertise but also about ethical intelligence. Understanding literacy extends beyond knowing how to upload content; it also encompasses understanding the reasons and correct ways to share content so as not to harm others. This famous book, written by KH Hasyim Asy'ari, serves as the "main guide" in Islamic boarding schools (pesantren) on ethics between teachers (alim) and students (muta'allim). This title utilizes the principles in the book as a moral guide for behavior in the digital world. According to KH Hasyim Asy'ari, we are invited to view mobile phones not simply as tools, but as a place for interaction between individuals where norms of politeness and divine values are still applied. On social media platforms, our "speech" is represented by our finger typing. The Quran reminds us to always speak in a manner that is good and correct.